Functionalisation of Halloysite Nanotube for the Development of Mixed Matrix Membrane - Bong, Yin Chung (Universiti Teknologi PETRONAS, 2016)
The success of MMM is highly dependent on the relative hydrophobicity of the inorganic filler and organic polymer chosen. In this work, the inorganic filler, halloysite nanotube (HNT) was functionalised to increase its hydrophobicity for a better yield of interfacial interaction with the polymer matrix, polyethersulfone (PES). In the result, the critical polymer concentration was determined to be at 25wt%. The critical polymer concentration obtained was set as the basis of MMM. The FT-IR result obtained confirmed that the HNT has been functionalised with the appearance of new peaks at 2938 cm-1 and 1502 cm-1 indicating the stretching and deformation of CH2; 1346 cm-1 and 1574 cm-1 indicating the deformation of NH2. The surface morphology SEM showed good filler dispersion for all MMMs whilst the cross sectional morphology showed a desirable fingerlike macrovoid formation in all membranes. However, the formation of void around the unmodified HNT was more prominent compared to functionalised HNT (m-AHNT).